2008
DOI: 10.1007/s11202-008-0049-1
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the algorithmic complexity of classes of computable models

Abstract: We estimate the algorithmic complexity of the index set of some natural classes of computable models: finite computable models (Σ 0 2 -complete), computable models with ω-categorical theories (Δ 0 ω -complex Π 0 ω+2 -set), prime models (Δ 0 ω -complex Π 0 ω+2 -set), models with ω 1 -categorical theories (Δ 0 ω -complex Σ 0 ω+1 -set). We obtain a universal lower bound for the model-theoretic properties preserved by Marker's extensions (Δ 0 ω ).While studying the structural properties of theories and the algebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In [6][7][8], it was shown that the given constructions allow of preserving the property of being prime and, as it is not hard to see, of being almost prime. The properties of being d-decidable for constructed models and of being d-autostable relative to d-strong constructivizations are also inherited.…”
Section: Reducing An Arbitrary Finite Signature To a Signature For Grmentioning
confidence: 99%
See 1 more Smart Citation
“…In [6][7][8], it was shown that the given constructions allow of preserving the property of being prime and, as it is not hard to see, of being almost prime. The properties of being d-decidable for constructed models and of being d-autostable relative to d-strong constructivizations are also inherited.…”
Section: Reducing An Arbitrary Finite Signature To a Signature For Grmentioning
confidence: 99%
“…PROPOSITION 1.1 [6][7][8]. For any finite relational signature σ, there exists a signature σ 1 that consists of a single predicate P and is such that for any model M of the signature σ, there exists a model M of the signature σ 1 such that: [6][7][8].…”
Section: Reducing An Arbitrary Finite Signature To a Signature For Grmentioning
confidence: 99%